Structural varieties of 2D boron nitride - D.S. Ryashentsev; M.E. Belenkov; L.Y. Kovalenko (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
Using the density functional theory method, geometric optimization of layered polymorphic varieties of boron nitride, in which atoms are located in three different structural positions, was carried out and their energy and electronic properties were determined. The structures of the new polymorphs consist of boron and nitrogen atoms in a sp2-hybridized state and were modeled from hexagonal boron nitride by introducing topological defects 4-6-8, 4-6-10, 4-8-10, 4-16 and 4-6-12. As a result of the analysis, the possibility of the existence of nine new structural varieties was established. However, during the geometric optimization process, three structures turned out to be unstable, which were transformed into more stable polymorphic varieties BN-L4-8 and BN-L4-6-8. The layer density of the considered polymorphic varieties varies from 0.651 to 0.727 g/cm2.The sublimation energy values of the new structures range from 16,93 to 17,69 eV/(BN). The band gap varies from 3,20 to 4,03 eV. The relationships between the energy and structural parameters are determined.